ANALISIS MATERIALITAS PADA PROSEDUR AUDIT VOUCHING ATAS AKUN BEBAN OPERASIONAL - Chrisna Putri, Rani; Sulistyowati, Erna (BALANCE: Jurnal Akuntansi, Auditing dan Keuangan, 2023)
In the era of society 5.0, the auditor profession will continue to exist even though the threat of AI (Artificial Intelligence) has come, bearing in mind that there are many human intelligences that cannot be replaced by any robots. An auditor needs to have an understanding of materiality, where this concept relates to how large a misstatement contained in an assertion can be accepted by the auditor so that users of financial statements are not affected by the magnitude of the misstatement. One of the applications of materiality is the vouching audit procedure. Vouching is a test carried out by the auditor to check the authenticity or correctness of the occurrence of a transaction presented in the financial statements through physical source documents. Vouching for operating expense accounts is important to do because there are many findings indicating irregularities in the presentation of operating expenses in the financial statements. The method used is a qualitative research-descriptive analysis based on the results of interviews with 4 people at Public Accounting Firms and Public ABC as samples and observations. This study aims to get answers regarding the importance of materiality in vouching audit procedures for operating expense accounts.